Dissonances in care: childhood, well-being, and the politics of welfare in Japan - Chapman, CR (2024)
Competing principles of child well-being drive reform in Japanese child welfare, a system undergoing an unprecedented shift from residential care to foster families. The change is notable because the system has remained largely the same since the post-war occupation. This thesis explores the social and cultural dimensions of child welfare politics. National debates center on how to care for children, ranging from defining children’s needs to enhancing practitioners’ skills, and coincide with burgeoning concern among authorities for the ever-growing rates of child abuse, mental illness, and disability. Through twelve months of ethnographic research in Tokyo, I worked with children, caregivers, caseworkers, and psychologists to contextualize discursive representations of care and children. I used visual and material methods as a modular platform for participation, an approach I call narrative storywork. Through photography and drawing, among other mediums, children narrated poignant stories about their care experiences. This thesis develops a theory of care politics by framing child protection in terms of spatial-material relations to offer new ways of understanding well-being and inequity in state care. Japanese child welfare is a disaggregated system; I emphasize polyvocality to illuminate the nuances between varied spaces of care practice, ranging from casework agencies to the side streets of group homes. Caseworkers prioritized objectivity by eschewing rapport with children, psychologists valued a professional, lived relationship, and caregivers esteemed strong affective bonds irrespective of proximity. Children, conversely, cared more about life outside of welfare and actively took care of themselves and others. With particular attention to the entanglements of people with government, biomedicine, and family, I argue that these spaces of practice do not altogether form a holistic vision of care, but a piecemeal assemblage of competing intentions and technologies. These dissonances speak to broader trends and lived tensions in the professionalization of casework, valorization of the nuclear family ideal, and local reconfiguring of health knowledge. The welfare system still does not help children achieve permanence as social relationships remain structurally bounded, yet it is the local level acts of care that mediate subjectivity that present the most significance for improving policy and practice.